B7-Positive and B7-Negative Acute Myeloid Leukemias Display Distinct T Cell Maturation Profiles, Immune Checkpoint Receptor Expression, and European Leukemia Net Risk Profiles - Antohe, Ion; Dǎscǎlescu, Angela; Dǎnǎilǎ, Cǎtǎlin; Titieanu, Amalia; Zlei, Mihaela; Ivanov, Iuliu; Sireteanu, Adriana; Pavel, Mariana; Cianga, Petru (Frontiers in Oncology, 2020)
Acute myeloid leukemia (AML) is generally considered a poorly immunogenic malignancy, displaying a “non-inflamed” leukemia microenvironment (LME), leading to T cell tolerance. However, the immune landscape of AML is much more heterogeneous. Since B7 expression is regarded as a consequence of an interferon-mediated “inflammatory” phenotype, we have investigated by flow cytometry the B7 checkpoint ligands B7.1, B7.2, programmed death ligand 1 (PD-L1), PD-L2, ICOS-L, B7-H3, and B7-H4 on the AML blasts of 30 newly diagnosed patients and their corresponding receptors [cytotoxic T lymphocyte-associated protein 4 (CTLA-4), programmed death 1 (PD-1), and inducible T cell costimulator (ICOS)] on bone marrow (BM) T cell maturation populations. We could thus evidence B7-negative and B7-positive leukemias either with an isolated expression or part of eight different checkpoint ligand “signatures” that always included an inhibitory B7 molecule. B7-positive AMLs encompassed intermediate and adverse European Leukemia Net (ELN) risk cases and displayed mainly central memory CD4+ T cells with high ICOS levels and effector CD8+ T cells with high PD-1 expression. B7-negative cases were rather classified as AML with recurrent genetic anomalies and displayed predominantly naive T cells, with the exception of NPM1 mutated AMLs, which expressed B7-H3. These different B7 immune profiles suggest that specific immunotherapies are required to target the distinct immune evasion strategies of this genetically heterogeneous disease.